Depression, anxiety, and stress among undergraduate dental students in Hyderabad City, Telangana, India: A cross-sectional study - Ambati Sravani; Dolar Doshi; Suhas Kulkarni; Padma Reddy; Srikanth Reddy (Wolters Kluwer Medknow Publications, 2018)
Introduction: Increased levels of psychological disturbances such as depression, anxiety, and stress (DAS) among dental students affect the way these students take care of patients. Aim: The aim of this study is to assess DAS among undergraduate dental students in Hyderabad city, Telangana, India. Materials and Methods: A short version of depression, anxiety, and stress scale was distributed to undergraduate dental students in four dental colleges. Comparison among the variables was done using ANOVA and Independent t-test. Results: The study group comprised 200 (23.7%) males and 645 (76.3%) females. The overall mean DAS score and its dimensions were not significant based on gender. Married students showed significantly more DAS compared to unmarried (P < 0.05). When the year of study was considered for all colleges together, the overall mean DAS score and its individual dimensions score were significantly high among III year students followed by IV, I, and II years (P < 0.05). Conclusion: Clinical years were more stressful than the nonclinical years. This suggests a need for special attention to the structure of the clinical program, particularly at the point of transition from the preclinical to the clinical phase.